The Effect of Mummy Extract on Matrix Protein Synthesis by Human Wharton's Jelly-Derived Stem Cells and Dermal Fibroblasts and Their Behavior on Plated PCL Scaffold - Sabetkam, Shahnaz; Khodaie, Sepideh Hassanpour; Rad, Jafar Soleimani; Roshangar, Leila (Aras Part Medical Int Press, 2025)
Objectives: Wound healing as a coordinated physiological mechanism is a critical issue in medicine. Despite numerous treatment methods, the slow-healing process and scar formation have led researchers to develop new, more effective therapeutic approaches. Here, we evaluated the matrix protein synthesis in human Wharton's jelly-derived stem cells and human fetal fibroblast cell line (HFFF-2) in the presence of Mummy extract. Furthermore, cell attachment to the polycaprolactone (PCL) scaffold was examined by electron microscopy. Materials and Methods: The effective, non-toxic dose of Mummy was determined using an MTT assay. Subsequently, cell proliferation on the PCL scaffold was assessed using the MTT assay. The expression of collagen I, III, and fibronectin was analyzed. Finally, cell attachment and morphology on a PCL scaffold were examined using scanning electron microscopy. Furthermore, cell proliferation and attachment on the PCL scaffold were reviewed using the MTT assay and electron microscopy, respectively. Results: The results showed that Mummy extract significantly enhanced cell proliferation and increased fibronectin expression in treated fibroblasts. Surprisingly, collagen type I and fibronectin increased significantly in the co-cultured group. Scanning electron microscopy confirmed that cells successfully penetrated and adhered to the PCL scaffold in both control and Mummy-treated groups. Conclusions: Taken together, our findings indicate that Mummy extract can positively influence the expression of key extracellular matrix (ECM) proteins and cell-scaffold attachment, suggesting its potential as a complementary approach for wound therapy strategies, warranting further in vivo investigation. This study provides the first in vitro evidence for the synergistic effect of Mummy extract and WJSC-fibroblast co-culture on enhancing ECM production in a 3D environment.
Keywords: Collagen; Mesenchymal stem cells; Mummy; Wharton's jelly; Wound healing